PENGARUH INSTAGRAM SOCIAL MEDIA MARKETING TERHADAP KEINGINAN BERKUNJUNG PASIEN DENGAN FAKTOR MEDIASI KEPERCAYAAN ONLINE DAN REPUTASI DOKTER PADA LAYANAN KLINIK JANTUNG RS X AREA - Kevin Tandiawan (Media Bina Ilmiah, 2024)
The lives of millions of people around the world are currently greatly influenced by technological developments. The large number of users of social media applications allows a relationship to occur between a product and customers. Social media activities have received special attention as an effective and efficient way to promote a business and attract customers. The number of cardiac polyclinic patients at Hospital X in the Banten area in 2023 will be 13,453 patients, with an average of 1121 patients per month. The aim of this research is to see what influences visit intention at Hospital X. This type of research is quantitative research with a survey of the population. This type of research is quantitative by conducting hypothesis and correlational tests. The population in this study was 390 samples. The results of this research are that the positive influences on visit intention are online trust, doctor's reputation, entertainment, interaction and e-WOM. So it is hoped that RS X can increase the entertainment factor, Instagram social media content so that it can increase visit intention.